Faktor-Faktor Yang Berhubungan Dengan Kejadian Kematian Maternal Di Solo Raya (Studi Kasus Di Rsud Dr. Moewardi Surakarta) - PRATAMA, MAHESA, Giat Purwoatmodjo, SKM, M.Kes, Anisa Catur Wijayanti, SKM, M.Epid (2016)
MMR in Indonesia is still quite high, amounting to 359 per 100,000 live births (IDHS 2012). AKI in Central Java in 2012 based on reports from county/city of 116.34/100,000 live births. Solo Raya is a region in Central Java with a fairly high maternal mortality. The purpose of this study was to determine the risk factors that influence the incidence of maternal mortality in Solo Raya years 2013-2015. This research method using analytic observational study design, the design or the design of case-control studies. This study population of 100 people, 50 cases and 50 controls. Data analysis was performed using univariate, bivariate with chi square test, multivariate multiple logistic regression method. The results of the bivariate analysis showed that the factors affecting maternal mortality is spaced pregnancies (p = 0.000) and the ANC examination (p = 0.014). While that is not a risk factor for maternal mortality is parity, where labor, and education. The results showed that the risk factors that influence maternal mortality by multivariate analysis were spaced pregnancies (p=0,001; OR=4,227; 95% CI=1,737 to 10,284).